The Pengaruh Profitabilitas Dan Leverage Terhadap Penghindaran Pajak (Tax Avoidance) Pada Masa Pandemi Covid-19 - A Restu Maulani; Nor Norisanti; Erry Sunarya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The research was aimed at determining the influence of probability and leverage toward tax avoidance during the COVID-19 pandemic implemented on foods and beverages subsector companies registered in Indonesia’s Stock Exchange. The research methods applied were descriptive and associative; samples taken by purposive sampling method and Nonprobability sampling were in terms of 15 out of 53 companies that complied with the criteria, so that samples that were studied were amounted to 45 data counted from quarter I to III of 2020. The techniques of collecting data deployed were secondary data that included documentation and literature study. The technique of analyzing data applied was multiple linear regression. Based on the results, the research shows that partially there is no significant influence from profitability toward tax avoidance, yet leverage partially does. Thus, simultaneously both profitability and leverage significantly influence tax avoidance altogether on foods and beverages subsector companies registered in the Indonesia’s Stock Exchange with its influence ratio amounted to 24.8%. Keywords: Profitabilty, Leverage, Tax Avoidance